Pembatasan Kebebasan Berpendapat Dan Berekspresi Di Sosial Media Berdasarkan Peraturan Perundang-Undangan Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik (ITE) - Nyoman Gede Antaguna; Anak Agung Sagung Laksmi Dewi (Kertha Wicaksana, 2023)
The rapid development of social media now a days is influenced by the tremendous advantage of information and technology, and the fact that every netizen is the owner of his social media account who can freely think and express as he wishes. This freedom is the implementation of this nation's acknowledgment of the human rights of every individual which has been stated firmly in the 1945 Constitution. However, there is a stipulation that this freedom should not violate the rights of others, who also carry out their human rights. For this reason, the state is standing in regulating the legitimation of its citizens perform on social media through the entity of Law Number 11 of 2008 concerning Information and Electronic Transactions as amended by Law Number 19 of 2016, hereinafter referred to as the Law on Information and Electronic Transactions (UU ITE), which some consider it as a provision that can limit freedom of opinion and expression as a democratic state justifies it. The ITE regime is considered to have the potential for bordering by threatening the suspect through imprisonment or a fine. For this reason, this scientific paper raises the issue of the nature of freedom of opinion and expression, the negative activities of netizens on sosial media based on popular cases in the Republic of Indonesia and the purpose of the restrictions on the ITE Law.